Understanding TikTok as an Asynchronous Learning Media in ESP: A Study among Business English Students - Efendi, Erfan; Aly, Abdul Hamid; Srinin, Wathanan (Langkawi: Journal of The Association for Arabic and English, 2025)
This study investigates the effectiveness of asynchronous learning via TikTok in teaching ESP, specifically Business English, among 112 undergraduate students at Universitas Islam Malang. Motivated by the growing role of digital platforms in language education, quantitative research design was employed, quantitative data collected through structured questionnaires and analyzed using SPSS. The results revealed high to very high student agreement across key variables: perceived ease of use (M = 4.45), learning comfort (M = 4.25), oral English practice effectiveness (M = 4.35), and confidence in language learning (M = 4.40), alongside positive ratings for creative engagement (M = 4.30) and collaborative learning potential (M = 4.15). These findings demonstrate that TikTok, as an asynchronous educational tool, supports language proficiency development, learner autonomy, and interactive engagement in ESP contexts. The study contributes to practice by providing empirical support for integrating familiar, student-centered technologies into ESP instruction, and to theory by extending digital pedagogy frameworks to include mobile social media as effective platforms for fostering self-directed and interactive language learning. Implications are offered for educators and policymakers aiming to innovate language instruction through contextually relevant digital tools.